Dampak Kecanduan Gadget Terhadap Kesehatan Mental Remaja Pada Siswa Kelas VII MTS Yabis Pasirlangu - Aprilaini, Desi Lia; Sari, Resti Okta (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is to explore the impact of gadget addiction on adolescent mental health, especially among class VII students. The phenomenon of excessive gadget use, especially among teenagers, is increasingly common. This research focuses on the effects on the mental health of class VII students at MTs Yabis Pasirlangu who are involved in gadgget addiction.